Investigating the Correlation of Microplastic Pollution Between Seawater and Marine Salt Using Micro-Raman Spectroscopy - Khuyen, Vo Thi Kim; Le, Dinh Vu; Anh, Le Hung; Fischer, Axel René; Dornack, Christina (Frontiers in Marine Science, 2021)
Microplastics (MPs) are synthetic polymer pieces with a size of less than 5 mm that are ubiquitous in the marine environment. They have been recently detected in several wild species and sea products. An indispensable condiment in human food is marine salt that is produced from seawater. Since toxicity studies report potential health impacts when plastic debris is ingested, more attention must be paid to the MP contamination of sea salt and the underlying reasons for this. The central aim of this study is to evaluate the MPs contamination level of sea salt in correlation with the MPs contamination level of seawater in Vietnamese areas. Micro-Raman spectroscopy was employed to determine MPs in the samples collected from three artificial salt pans of Vietnam. The result revealed the presence of MPs in all study areas—Vung Tau (VT;14.54 MPs/L seawater and 114.67 MPs/kg salt), Ly Nhon (LN; 13.14 MPs/L seawater and 63.59 MPs/kg salt), and Can Thanh (9.42 MPs/L seawater and 93.69 MPs/kg salt). The comparisons highlight close correlations in the percentage, shape, size, and color of MPs, especially polyethylene, polyethylene terephthalate, and polypropylene particles extracted from the seawater and its salt. This study proved that seawater is a plastic pollution source for salts produced by traditional seawater evaporation. The study also alerts the prevalence of MPs in the environment and human consumables, thereby indicating that actions must be taken to reduce the pollution of water sources in Vung Tau and at the UNESCO Can Gio Mangrove Biosphere Reserve and improve salt production and refinery processes in order to minimize the number of MPs in final salt products for safe consumption.